Does Elastic Resistance Affect Finger Pinch Discrimination?. (October 2013) - Han, Jia; Waddington, Gordon; Anson, Judith; Adams, Roger
Objective: The sensitivity of pinch movement discrimination between the thumb and index finger was assessed with and without elastic resistance. Background: Researchers have examined the effect of elastic resistance on control of single upper-limb movements; however, no one has explored how elastic resistance affects proprioceptive acuity when using two digits simultaneously in a coordinated movement. Method: For this study, 16 right-handed, healthy young adults undertook an active finger pinch movement discrimination test for the right and left hands, with and without elastic resistance. We manipulated pinch movement distance by varying the size of the object that created the physical stop to end the pinch action. Results: Adding elastic resistance from a spring to the thumb–index finger pinch task did not affect accuracy of pinch discrimination measured as either the just noticeable difference, F (1, 15) = 1.78, p = .20, or area under the curve, F (1, 15) = 0.07, p = .80. Conclusion: Having elastic resistance to generate lever return in pincers, tweezers, and surgical equipment or in virtual instruments is unlikely to affect pinch movement discrimination. Application: Elastic resistance did not affect finger pinch discrimination in the present study, suggesting that return tension on equipment lever arms has a practical but not perceptual function. An active finger pinch movement discrimination task, with or without elastic resistance, could be used for hand proprioceptive training and as a screening tool to identify those with aptitude or decrements in fine finger movement control.